Environmental issues of Cantho Pesticide Factory Cantho province, Vietnam - Le Hoang Viet; Reutergardh, Lars Beitil; Stoll, Uwe; Heredia, Juan B.; Swiss Government; Swedish International Development Authority (Bangkok : Asian Institute of Technology, 1995)
The environmental impact of Pesticide Factories is one of the most important environmental issues in South-Vietnam. Therefore, an environmental audit with the focus on the wastewater (WW) characteristics was conducted at Cantho Pesticide Factory (CPF) in order to identify the sources and characteristics of pollutants and to find the way to solve the problems. The water consumption and WW discharged from canteen, toilet, bottle washing, floor cleaning, hand washing, wet-scrubber of this factory were measured to making a water balance. The WW discharged from toilet and canteen are considered as household WW, so that they were not characterized in this study. The water samples at five sampling stations were taken for analysing pH, conductivity, colour, COD, BOD, SS, TDS, and pesticide concentration. In addition, the other sources of pollutants were also recorded from existing data and the author's inspections. They are pesticide contaminated packs discharged from packaging process, used drums, dust, volatile organics, used xylene. Besides, general data on Vietnamese Pesticide Industry such as institution, legislation, regulation were collected and compared with available data of Thailand. \. The WW generated from production activities were discharged in small volume (5.9 m3/d). The bottle washing WW is not contaminated by pesticides and the pH, colour, COD, BOD, SS, TDS in order of 7.26, 55 (Pt-Co scale), 218 mg/L, 52 mg/L, 86 mg/L, 522 mg/L respectively. The pesticides contaminated WW were discharged of 2.14 m3/d. Among these WW floor cleaning waste water is the most polluted one. In Bassa production day, it has pH, colour, COD, BOD, SS, TDS and Bassa concentration in order of 5.59, 2533 (Pt-Co scale), 7853 mg/L, 640 mg/L, 82 mg/L, 6698 mg/Land 1176 mg/L respectively. This kind of WW shares only 12% of total WW generated by production activities, but it contributes 63% to total daily COD and 49% to total daily TDS discharged. These WW are quite able to be completely treated by existing chemical WW treatment system due to high alkaline condition and long retention time (if this system was properly operated). The improvements of WW treatment system such as separating the drainage pipe for free-pesticide WW, making a transparent roof, and raising the wall of treatment tank are proposed for the factory. ln addition, installing a packed column and enlarging the pipe head of wet-scrubber are also suggested. The preliminary financial analysis were made and the results showed that proposed measure is marginally financial attractiveness because it too sensitive to the fluctuation of benefit. But the proposed measures should be implemented due to there are many intangible benefit such as to lower the risk of abortion in females worker and inquire cancer. The study went to the conclusion that the environmental issues in Cantho Pesticide Factory are due to the poor planning, management, lack awareness about the course effect relationship of the pollutants to the environment and the design and operation of treatment facilities.
Thesis (M. Sc.) - Asian Institute of Technology, 1995
A thesis submitted in pa1tial fulfilment of the requirements for the degree of Master of Science
Keywords: Factory and trade waste -- Environmental aspects -- Vietnam -- Can Tho